Aspects of reproduction in the four-striped field mouse, Rhabdomys pumilio - Jackson, Claire (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2000)
Rhabdomys pumilio, in the Eastern Cape of South Africa, does not use short day length as an inhibitory cue for reproductive activity, and, despite previous records indicating that these mice are strictly seasonal in their reproduction, litters have been found during the winters of some years,both in the Eastern Cape and in the Western Cape. This led me to believe that the reproductive activity of Rhabdomys pumilio is more opportunistic and that the cue or cues used to control reproduction are less predictable and, or more variable than the photoperiod cue used by many seasonally reproducing rodents. Two experiments were conducted, investigating the influence of low ambient temperature (15â °C)and reduced food availability on the reproductive activity of both male and female four striped field mice. Mice were maintained in one of four conditions (food restricted at 15â °C, food restricted at 26â °C, ad lib. food at 15â °C, and ad lib. food at 26â °C) for 4 (males) and 8 weeks (females)(photoperiod 12L:12D, humidity 40%). Results indicated that the males reduced their reproductive activity slightly when exposed to either low temperature or low food availability and that maximum inhibition of reproduction occurred when mice were exposed to both low temperature and low food availability. However, female reproductive activity was inhibited when exposed to low food availability, irrespective of the temperature. Both sexes of mice showed varying abilities to resist fat loss and, in the males, the size of the fat store had a significant effect on reproduction. This varying ability to resist fat loss could be related to levels of activity and in the females (where activity was quantified), high activity scores were significantly associated with reproductive inhibition. These results support the hypothesis that reproduction in Rhabdomys pumilio is opportunistic and controlled by the availability of energy. I propose that the females will be more sensitive to reproductive inhibition due to their far greater post-fertilization responsibilities, where the reproductive activity of the females is rapidly inhibited by a reduction in food availability, while the males are less readily inhibited by low food availability or low temperature, unless the change in the controlling factors is severe enough, or prolonged, at which stage their reproductive activity will cease. The significance of opportunistic reproduction in the seasonal but unpredictable climate of the study area is discussed.
Keywords: Microtus; Mice; Mice -- Reproduction